2021
DOI: 10.1155/2021/7507555
|View full text |Cite|
|
Sign up to set email alerts
|

Fabrication of a Lead Head Made of the Carbon-Fiber-Reinforced Composite for the Temporary Cardiac Pacemaker

Abstract: Compared with traditional leads, carbon fiber composite leads have a series of advantages such as lightweight, soft texture, and high conductivity. In this experiment, we attempted to improve the existing carbon-fiber-based TTCP metal leads by using carbon-fiber-graphene-woven leads or conductive cloth, so as to solve a series of defects of TTCP metal leads commonly used in the clinical temporary cardiac pacemaker. We performed a series of measurements, including resistance comparisons and stability checks on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Besides signal acquisition, conductive fibers can also be used as temporary pacing wires for correcting abnormal heart rates. Zhou et al [ 166 ] attempted to improve the existing carbon-fiber-based temporary transvenous cardiac pacing metal leads by using carbon-fiber-graphene-woven leads or conductive cloth. The results showed that the carbon fiber bundle was stable and easily deformed under lower stress to reduce the damage to the myocardium, which demonstrates excellent clinical application value.…”
Section: Conductive Fibers In Implantable Bioelectronicsmentioning
confidence: 99%
“…Besides signal acquisition, conductive fibers can also be used as temporary pacing wires for correcting abnormal heart rates. Zhou et al [ 166 ] attempted to improve the existing carbon-fiber-based temporary transvenous cardiac pacing metal leads by using carbon-fiber-graphene-woven leads or conductive cloth. The results showed that the carbon fiber bundle was stable and easily deformed under lower stress to reduce the damage to the myocardium, which demonstrates excellent clinical application value.…”
Section: Conductive Fibers In Implantable Bioelectronicsmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%